2023
DOI: 10.3389/fchem.2023.1233151
|View full text |Cite
|
Sign up to set email alerts
|

On photokinetics under monochromatic light

Mounir Maafi

Abstract: The properties of photokinetics under monochromatic light have not yet been fully described in the literature. In addition, for the last 120 years or so, explicit, handy model equations that can map out the kinetic behaviour of photoreactions have been lacking. These gaps in the knowledge are addressed in the present paper. Several general features of such photokinetics were investigated, including the effects of initial reactant concentration, the presence of spectator molecules, and radiation intensity. A un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(25 citation statements)
references
References 59 publications
3
22
0
Order By: Relevance
“…The phototransformation mechanisms studied in the present contribution are worked out from the -shaped reaction mechanism described in a previous study ( Maafi, 2023 ). Special attention is dedicated to the photomechanisms that operate most of the known organic actinometers ( Kuhn et al, 2004 ; Braslavsky, 2007 ), as shown in Scheme 1 .…”
Section: Experimentalsmentioning
confidence: 99%
See 2 more Smart Citations
“…The phototransformation mechanisms studied in the present contribution are worked out from the -shaped reaction mechanism described in a previous study ( Maafi, 2023 ). Special attention is dedicated to the photomechanisms that operate most of the known organic actinometers ( Kuhn et al, 2004 ; Braslavsky, 2007 ), as shown in Scheme 1 .…”
Section: Experimentalsmentioning
confidence: 99%
“…The number of photons entering the reactor ( ) is measured as a sum of the number of photons delivered at each wavelength ( , in ). The detailed derivation of (expressed in ) was previously provided ( Maafi, 2023 ). This number of photons will naturally depend on both the span of wavelength ( ) considered for the measurement and the profile of the lamp ( ) used for irradiation.…”
Section: Experimentalsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2005, a landmark publication from Booker-Milburn and Berry (GSK) et al described a photochemical plug flow reactor (PFR) using readily available fluorinated ethylene propylene (FEP) tubing and mercury broad-spectrum lamps and subsequently sparked a renaissance in photochemistry . Coupled with the advent of cheaper monochromatic light sources, i.e., light emitting diodes (LEDs), there has been an explosion in new chemical transformations reported in the literature, from both academia and the pharmaceutical industry. As these new transformations are implemented into the construction of active pharmaceutical ingredients (APIs), a perennial question arises: how do you scale photochemical transformations? Continuous flow chemistry has received much attention for scaling photochemistry due to the increased surface area to volume ratio which satisfies issues around the penetration of light (Beer–Lambert law) and the intensity of light (Bunsen–Roscoe law). , As intimated above, there are added complexities to reactor design for photochemistry, and both light penetration and the use of heterogeneous catalysis remain unresolved issues when designing reactors. In recent years, different types of reactors have been described in the literature as a solution to performing photochemistry on scale. These reactors tend to follow a PFR design (Figure a), although the design of immersive modular photoreactors with static mixing has recently been reported to increase mass transfer in the system .…”
Section: Introductionmentioning
confidence: 99%
“…12 Continuous flow chemistry has received much attention for scaling photochemistry due to the increased surface area to volume ratio which satisfies issues around the penetration of light (Beer−Lambert law) and the intensity of light (Bunsen−Roscoe law). 13,14 As intimated above, there are added complexities to reactor design for photochemistry, and both light penetration and the use of heterogeneous catalysis remain unresolved issues when design-ing reactors. In recent years, different types of reactors have been described in the literature as a solution to performing photochemistry on scale.…”
Section: ■ Introductionmentioning
confidence: 99%